Simplify 9x+3y−6−5x+4y−3 .

3 answers

To simplify the expression \( 9x + 3y - 6 - 5x + 4y - 3 \), we can combine like terms.

  1. Combine the \( x \) terms: \[ 9x - 5x = 4x \]

  2. Combine the \( y \) terms: \[ 3y + 4y = 7y \]

  3. Combine the constant terms: \[ -6 - 3 = -9 \]

Putting it all together, the simplified expression is: \[ 4x + 7y - 9 \]

Simplify 9/11z − 4/11z .

To simplify the expression \( \frac{9}{11}z - \frac{4}{11}z \), we can combine the terms since they have the same denominator.

  1. Combine the coefficients of \( z \): \[ \frac{9}{11}z - \frac{4}{11}z = \left(\frac{9 - 4}{11}\right)z = \frac{5}{11}z \]

So, the simplified expression is: \[ \frac{5}{11}z \]